Relationship between Risk Factors and Drug Use among Female Prisoners in Semarang Prison between 2012 and 2013 - Ahmadi NH, Ahmadi NH; Fitri, Ratna; Elly NH, Elly NH (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
Drugs abuse is a complex problem facing family and society. Drug abuse cases have long long been recognized. in Indoneisia the cases started to gain public attention in 1969. Today, the similiar cases are increasing in number. There have been more number cases and type of drugs abused (multiple drugs). The Risk factors for drug abuse vary among individuals and involve several factors namely individual, environment and drugs. The interaction of the three factors leads to the drug abuse. To cope with that, a holistic approach is needed. This study was aimed at dinding out the risk factors for drug abuse among women serving in women prison of Semarang due to drug abuse. In this cross-sectional study, chi square test was applied to assess the correlation between the risk factors and the drug abuse. Cooficient contigency was applied to evaluate the degree of correlation among variables. The result showed that out of 273 women prisoners, 176 were drug abusers. The individual factors of enxiety had a normal possitive correlation with drug abuse with a weak correlation (p<0,05, r=0,221.)